Design of Heading Fault-Tolerant System for Underwater Vehicles Based on Double-Criterion Fault Detection Method - Wei, Yanhui; Liu, Jing; Hao, Shenggong; Hu, Jiaxing (Journal of marine science and application, 2019)
This paper proposes a heading fault tolerance scheme for operation-level underwater robots subject to external interference. The scheme is based on a double-criterion fault detection method using a redundant structure of a dual electronic compass. First, two subexpansion Kalman filters are set up to fuse data with an inertial attitude measurement system. Then, fault detection can effectively identify the fault sensor and fault source. Finally, a fault-tolerant algorithm is used to isolate and alarm the faulty sensor. The program can effectively detect the constant magnetic field interference, change the magnetic field interference and small transient magnetic field interference, and conduct fault tolerance control in time to ensure the heading accuracy of the system. Test verification shows that the system is practical and effective.